If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + m + -6 = 0 Reorder the terms: -9 + -6 + m = 0 Combine like terms: -9 + -6 = -15 -15 + m = 0 Solving -15 + m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + m = 0 + 15 Combine like terms: -15 + 15 = 0 0 + m = 0 + 15 m = 0 + 15 Combine like terms: 0 + 15 = 15 m = 15 Simplifying m = 15
| 3x+2=2x-2 | | 2x^3+13x^2+21x=0 | | 3x+8=58-2x | | 2x^3+13x^2+21x=o | | 6-(1-6m)=23 | | 2-8v=2v+9 | | 3.4(s-5)-2.1=8.1 | | 12.4-2.8(x+3)=-12.8 | | 4v+8=6+10 | | 1.3(a+2)+5.6=17.3 | | 6x^2-55x+7=-2 | | 5.1-4.2(r+1)=-20.1 | | y=4x^2-12x+15 | | 2+3y=8y-18 | | 3-5(2x-5)=-2 | | 3(2x-1)+x=5x+3 | | -2b+7-3b=3 | | 0.004x=0.8 | | x^2-7x+1=-5 | | 7x^2+4x+9=0 | | 10t+(5t-4)=9t+(6t+2) | | x-3=27 | | x-1-3(5-2x)=2(2x-5) | | 3x^2+5x-28=0 | | 12x+9=9x-6 | | (4x+52)=(11x+17) | | 3.7y-31.5-1.9y=13.5 | | (5x+49)=(2x+33) | | 65=-4(x-5)-5x | | 5.8m-3.7m-8.6=6.1 | | x^2-8= | | .80(-80+65)=.66666666(54-72) |